Penerapan Model Pembelajaran Kooperatif Tipe STAD dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas II SDN 211/IX Mendalo Indah Muaro Jambi - Henky Setiadi; Prayitno Agustinus Sitanggang; Marnas Marnas (Universitas Batanghari Jambi, 2026)
This study was conducted as a collaborative Classroom Action Research (CAR) carried out in two cycles, namely Cycle I and Cycle II, and preceded by a pre-cycle stage. Each stage involved planning, implementation, observation, and reflection, with the aim of improving mathematics learning outcomes among second-grade students at SD Negeri 211/IX Mendalo Indah, Muaro Jambi. The instructional approach applied in this study was a cooperative learning model of the Student Teams Achievement Divisions (STAD) type. The research subjects consisted of 14 second-grade students, comprising 7 boys and 7 girls. Data on students’ mathematics learning outcomes were collected through test techniques administered at the end of each cycle. Based on the data analysis, the results indicate a significant improvement in students’ mathematics learning outcomes following the implementation of the STAD model, with the percentage of learning mastery increasing from 36% in the pre-cycle stage to 57% in the first cycle and reaching 93% in the second cycle.